Battery positive electrode material, battery and preparation method thereof

By using the melt diffusion method of purple-sulphur-based conjugated porous polymer/carbon nanotube composite (TCV@CNT) and sublimated sulfur in the positive electrode material of lithium-sulfur battery, the problem of poor capacity attenuation and cycle stability caused by the shuttle effect of lithium-sulfur batteries is solved, faster electron transmission and effective conversion of lithium polysulfide are achieved, and the overall electrochemical performance of the battery is improved.

CN119920839AActive Publication Date: 2025-05-02安徽国轩新能源汽车科技有限公司

Patent Information

Application Number
CN202510082336.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-05-02
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The shuttle effect caused by the dissolution and migration of lithium polysulfide of lithium polysulfide leads to rapid attenuation of battery capacity and poor cycling stability.

Method used

The violet-based conjugated porous polymer is used as the positive electrode material of lithium-sulfur battery, and the positive electrode material of the carbon nanotube is grown through solvothermal reaction to form a violet-based conjugated porous polymer/carbon nanotube composite material (TCV@CNT), and mixed with sublimated sulfur by melt diffusion method to prepare the positive electrode material of the battery S/TCV@CNT. The material can efficiently capture soluble lithium polysulfide and catalyze its redox conversion, inhibiting the shuttle effect.

Benefits of technology

It improves the electronic transmission capacity of lithium-sulfur batteries, catalyzes the conversion of lithium polysulfide, accelerates its conversion rate during discharge and charging, and improves the electrochemical performance and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920839A_ABST
    Figure CN119920839A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium-sulfur battery materials, and particularly discloses a battery positive electrode material, a battery and a preparation method of the battery positive electrode material. The preparation method comprises the following steps: S1, adding cyanuric chloride, V.2Cl and a carbon nanotube CNT into a solvent, carrying out solvothermal reaction, growing a viologen-based conjugated porous polymer on the surface of the carbon nanotube CNT in an in-situ directional polymerization manner, and recording as TCV-CNT; and S2, grinding and mixing the TCV-coated CNT and sublimed sulfur, adding the mixture into a reaction kettle, filling argon, and vulcanizing through a melt diffusion method to obtain the battery positive electrode material recorded as S / TCV-coated CNT. Compared with a material physically mixed by TCV and CNT, the synthesis method is simple, repeated preparation is easy, raw materials are easy to obtain and cheap, and the prepared positive electrode composite material (TCV-CNT) has higher electron transmission capacity, can catalyze conversion of lithium polysulfide, accelerates the conversion rate of lithium polysulfide in the discharging and charging processes, and has good application prospects. And the overall electrochemical performance of the lithium-sulfur battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano materials and lithium-sulfur batteries, and in particular to a battery positive electrode material, a battery and a preparation method thereof. Background Art

[0002] Due to limitations in energy density and other factors, lithium-ion batteries can no longer meet the energy storage needs of future advanced transportation, portable devices and residential applications. Lithium-sulfur (Li-S) batteries can provide 1675mAh g -1 High theoretical specific capacity and 2600Wh kg -1 The energy density of lithium-sulfur batteries is three to five times that of traditional lithium-ion batteries. In addition, sulfur is abundant in the earth's crust and is low in cost, making lithium-sulfur batteries one of the next generation of rechargeable batteries with great application prospects. However, there are still many problems and challenges in the commercial application of lithium-sulfur batteries. Among them, the shuttle effect caused by the dissolution and migration of lithium polysulfide leads to rapid attenuation of battery capacity and poor cycle stability. In order to solve these problems, scientific researchers have done a lot of exploration and research on positive electrode materials.

[0003] Based on this, we constructed viologen-based conjugated porous polymers as positive electrode carriers for lithium-sulfur batteries. Conjugated porous polymers are a type of porous organic polymer materials constructed by covalent bonds, with rich polar functional groups and permanent pores. The network structure of the conjugated porous polymer containing a large π-conjugated system is completely composed of light elements and has good electrochemical stability. In situ polymerization and growth on the surface of the conductor can facilitate the rapid transfer of electrons and obtain a higher mass specific capacity. The rich viologen polar functional groups in the viologen-based conjugated porous polymer can efficiently capture soluble lithium polysulfides, and the presence of lithium-philic and sulfur-philic groups can also catalyze the redox transformation of lithium polysulfides, thereby inhibiting the shuttle effect. Therefore, the development of efficient, simple, easy to synthesize and easy to repeat viologen-based conjugated porous polymers as efficient positive electrode sulfur carrier materials is something that everyone needs to study. Summary of the invention

[0004] One of the purposes of the present invention is to provide a method for preparing a positive electrode material for a battery. The prepared positive electrode material for a battery has a faster electron transmission capability, can catalyze the conversion of lithium polysulfide, accelerate the conversion rate of lithium polysulfide during discharge and charge, and improve the overall electrochemical performance of a lithium-sulfur battery. The synthesis method is simple and easy to prepare repeatedly, and the raw materials are cheap and readily available.

[0005] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a positive electrode material for a battery, comprising the following steps:

[0006] S1. Take 1,1'-bis(4-aminophenyl)-[4,4'-bipyridyl]-1,1'-diammonium chloride and record it as V·2Cl. Add cyanuric chloride, V·2Cl and carbon nanotubes (CNT) into a solvent and mix them evenly. Solvothermal reaction occurs. Viologen-based conjugated porous polymer grows on the surface of carbon nanotubes (CNT) by in-situ directional polymerization. The product is recorded as TCV@CNT.

[0007] S2. Grind TCV@CNT and sublimated sulfur and add them into a reactor, fill the reactor with protective gas, and sulfurize TCV@CNT by melt diffusion method to obtain a battery positive electrode material, which is recorded as S / TCV@CNT.

[0008] Further improvement of the preparation method of battery positive electrode material:

[0009] Preferably, in step S1, cyanuric chloride, V·2Cl and carbon nanotubes CNT are mixed in a mass ratio of 1:3.35:3.7, and then anhydrous ethanol and DMF are added as solvents, and the volume ratio of anhydrous ethanol to DMF in the solvent is 3:2.

[0010] Preferably, in step S1, the temperature of the solvothermal reaction is 120° C., the reaction time is 3 days, and after cooling to room temperature, the mixture is filtered to obtain black powder TCV@CNT.

[0011] Preferably, in step S2, TCV@CNT and sublimated sulfur are ground and mixed in a mass ratio of 4:6.

[0012] Preferably, in step S2, the reactor is a stainless steel reactor lined with polytetrafluoroethylene, the reaction temperature in the reactor is 155° C., and the reaction time is 12 h.

[0013] A second object of the present invention is to provide a battery positive electrode material prepared by the method for preparing the battery positive electrode material described in any one of the above.

[0014] The third object of the present invention is to provide a lithium-sulfur battery made from the above-mentioned battery positive electrode material.

[0015] The fourth object of the present invention is to provide a preparation method of the above-mentioned lithium-sulfur battery, comprising the following steps: grinding and mixing the battery positive electrode material S / TCV@CNT and the binder PVDF in a mass ratio of 9:1, adding N-methylpyrrolidone, grinding evenly to obtain a paste mixture, scraping the paste mixture onto a carbon paper current collector, and drying at 50-60°C for 10-12 hours to obtain a positive electrode sheet; assembling with a diaphragm, a negative electrode sheet, and a battery electrolyte in a glove box with a protective atmosphere to obtain a lithium-sulfur battery.

[0016] As a further improvement of the preparation method of the above lithium-sulfur battery:

[0017] Preferably, the battery electrolyte contains 1.0 mol L -1 The concentration of LiTFSI was 0.1 mol L -1 The solvent is a mixture of dioxolane DOL and ethylene glycol dimethyl ether DME in a volume ratio of 1:1.

[0018] Preferably, the separator used is the commercial Celgard 2400 type, and the negative electrode sheet used is a commercial lithium sheet.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1) The present invention provides a method for preparing a positive electrode material for a battery, wherein cyanuric chloride and V·2Cl solvent are subjected to a thermal reaction to grow a viologen-based conjugated porous polymer on the surface of a carbon nanotube (CNT) by directional polymerization, and the viologen-based conjugated porous polymer is used as a high-efficiency sulfur host material (TCV@CNT); and then TCV@CNT and sublimated sulfur are used to prepare a positive electrode material for a battery (S / TCV@CNT) by a melt diffusion method. The raw materials for the synthesis of the material are readily available and inexpensive, and the synthesis method is simple and easy to prepare repeatedly.

[0021] 2) When preparing TCV@CNT, cyanuric chloride, V·2Cl and carbon nanotubes (CNTs) are mixed in a mass ratio of 1:3.35:3.7, which can enable the ligand to be in situ polymerized and grown on the CNT surface, avoiding the aggregation of low-conductivity viologen-based conjugated porous polymers, increasing the transfer rate of interfacial electrons during battery charging and discharging, and helping to confine lithium polysulfide on the positive electrode side, thereby increasing the battery capacity.

[0022] 3) When preparing TCV@CNT, anhydrous ethanol and DMF are mixed in a volume ratio of 3:2 as a solvent, which is cheap and low in price.

[0023] 4) When preparing the battery positive electrode material S / TCV@CNT, TCV@CNT and sublimated sulfur are ground and mixed in a mass ratio of 4:6. Mixing according to this mass ratio can ensure the overall conductivity of the positive electrode material, improve the utilization rate of active sulfur, and alleviate the capacity attenuation during the cycle.

[0024] 5) When preparing the battery positive electrode material S / TCV@CNT, the reason for choosing a stainless steel reactor lined with polytetrafluoroethylene is that polytetrafluoroethylene has excellent corrosion resistance and can resist corrosive substances that may be produced during the reaction, protecting the reactor from damage. The reason for designing the reaction temperature and time is to put the active sulfur in a molten state and let it sink into the pores of the polymer, which is conducive to the adsorption of lithium polysulfide during the charge and discharge process.

[0025] 6) The battery positive electrode material S / TCV@CNT prepared by the present invention has faster electron transmission ability and can catalyze the conversion of lithium polysulfide.

[0026] 7) The battery positive electrode material S / TCV@CNT prepared in the present invention can be used in the preparation of lithium-sulfur batteries due to its properties.

[0027] 8) The present invention also discloses a method for preparing a lithium-sulfur battery, wherein a positive electrode sheet is prepared by using S / TCV@CNT, and after being assembled with a separator, a negative electrode sheet, and a battery electrolyte, a 2025-type button is obtained. The positive electrode sheet made of S / TCV@CNT can be used to accelerate the conversion rate of lithium polysulfide during discharge and charging, and improve the overall electrochemical performance of the lithium-sulfur battery.

[0028] 9) The electrolyte of the lithium-sulfur battery used in the present invention contains 1.0 mol L -1 The concentration of LiTFSI was 0.1 mol L -1 The solvent is a mixture of DOL and DME in a 1:1 volume ratio. This is because: LiTFSI is a lithium salt with high ionic conductivity and its high concentration in the electrolyte (1.0 mol L -1 ) helps to improve the ion conduction rate of the battery, thereby improving the battery's charge and discharge performance and power density; the addition of LiNO3 can be used as an additive to help form a stable protective film on the surface of the lithium metal negative electrode, reducing the formation and growth of lithium dendrites, thereby improving the battery's cycle stability and safety; the mixed solvent system of DOL and DME has a lower viscosity and a higher dielectric constant, which is beneficial to the migration of lithium ions and the transfer of charges, thereby improving the battery's rate performance.

[0029] 10) The present invention uses commercial Celgard 2400 type diaphragm and commercial lithium sheet, because: Celgard 2400 type diaphragm has excellent electrolyte wetting performance, can effectively improve the conductivity and power density of the battery, thereby improving the charge and discharge performance of the lithium-sulfur battery, the diaphragm can maintain stable performance in a high temperature environment, is not easy to deform or melt, and improves the safety and reliability of the battery. At the same time, its high strength and tear resistance can effectively prevent short circuits and leakage inside the battery, and extend the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The solid-state NMR carbon spectrum of the viologen-based conjugated porous polymer (TCV) prepared in Example 1;

[0031] Figure 2 TEM image of TCV@CNT prepared in Example 1;

[0032] Figure 3 CV curves of a symmetrical battery assembled from TCV@CNT in step S1 of Example 1, TCV+CNT in Comparative Example 3, untreated CNT, and TCV in Comparative Example 3;

[0033] Figure 4 The charge and discharge cycles of S / TCV@CNT of Example 1, S / TCV+CNT of Comparative Example 3, S / CNT of Comparative Example 1 and S / TCV of Comparative Example 2 at 0.2C. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0035] Comparative Example 1

[0036] This comparative example provides a method for preparing a positive electrode composite material S / CNT, and the specific steps are as follows:

[0037] Carbon nanotubes (CNT) and sublimated sulfur were ground and mixed in a mass ratio of 4:6, and added into a polytetrafluoroethylene-lined stainless steel reactor filled with argon. The mixture was kept at a constant temperature of 155°C for 12 hours and then cooled to room temperature by the melt diffusion method to obtain sulfurized carbon nanotubes, which were recorded as S / CNT.

[0038] Comparative Example 2

[0039] This comparative example provides a method for preparing a positive electrode composite material S / TCV, and the specific steps are as follows:

[0040] S1. Take 1,1'-bis(4-aminophenyl)-[4,4'-bipyridyl]-1,1'-diammonium chloride, record it as V·2Cl, add 0.03 mol of cyanuric chloride and 0.045 mol of V·2Cl into a solvent, and mix them evenly. The solvent is prepared by mixing 1.5 ml of anhydrous ethanol and 1 ml of DMF. Keep the temperature at 120°C for 3 days to cause a solvothermal reaction. After cooling to room temperature, filter and obtain a brown powder, which is a viologen-based conjugated porous polymer (TCV);

[0041] S2. TCV and sublimed sulfur were ground and mixed in a mass ratio of 4:6, and placed in a polytetrafluoroethylene-lined stainless steel reactor filled with argon. The mixture was kept at a constant temperature of 155°C for 12 hours and cooled to room temperature by a melt diffusion method to prepare a sulfurized viologen-based conjugated porous polymer, which was recorded as S / TCV.

[0042] Comparative Example 3

[0043] This comparative example provides a method for preparing a positive electrode composite material S / TCV+CNT, and the specific steps are as follows:

[0044] S1. Take 1,1'-bis(4-aminophenyl)-[4,4'-bipyridyl]-1,1'-diammonium chloride, record it as V·2Cl, add 0.03 mol of cyanuric chloride and 0.045 mol of V·2Cl into a solvent, and mix them evenly. The solvent is prepared by mixing 1.5 ml of anhydrous ethanol and 1 ml of DMF. Keep the temperature at 120°C for 3 days to cause a solvothermal reaction. After cooling to room temperature, filter and obtain a brown powder, which is a viologen-based conjugated porous polymer (TCV);

[0045] S2. TCV, carbon nanotubes CNT and sublimated sulfur were physically ground and mixed in a mass ratio of 1.33:2.66:6, and placed in a polytetrafluoroethylene-lined stainless steel reactor filled with argon. The mixture was kept at a constant temperature of 155°C for 12 hours and cooled to room temperature by the melt diffusion method to prepare sulfurized viologen-based conjugated porous polymers and carbon nanotubes, which were recorded as S / TCV+CNT.

[0046] As a control, TCV and carbon nanotubes CNT were physically ground and mixed at a mass ratio of 1.33:2.66 to obtain blended TCV and CNT, which was recorded as TCV+CNT.

[0047] Example 1

[0048] This comparative example provides a method for preparing a positive electrode composite material S / TCV@CNT, and the specific steps are as follows:

[0049] S1. Take 1,1'-bis(4-aminophenyl)-[4,4'-bipyridyl]-1,1'-diammonium chloride and record it as V·2Cl. Mix cyanuric chloride, V·2Cl and CNT in a mass ratio of 1:3.35:3.7. Add 2.1ml anhydrous ethanol and 1.4ml DMF as solvents. Keep the mixture at 120°C for 3 days to cause solvothermal reaction. After cooling to room temperature, filter and obtain black powder. The black powder is viologen-based conjugated porous polymer grown on the surface of carbon nanotubes CNT by in-situ directional polymerization, which is recorded as TCV@CNT.

[0050] S2. Grind and mix TCV@CNT and sublimated sulfur in a mass ratio of 4:6, place in a polytetrafluoroethylene-lined stainless steel reactor filled with argon, and use the melt diffusion method to keep the temperature at 155°C for 12 hours. After cooling to room temperature, sulfurized TCV@CNT is prepared, which is the battery positive electrode material S / TCV@CNT.

[0051] The positive electrode composite materials (S / TCV@CNT, S / TCV+CNT, S / CNT, S / TCV) prepared in Comparative Examples 1-3 and Example 1 were ground and mixed with the binder PVDF at a mass ratio of 9:1, and N-methylpyrrolidone NMP was added dropwise and ground evenly into a paste. The paste mixture was scraped onto a carbon paper current collector and dried at 60°C for 12 hours to be used as a positive electrode sheet; the selected battery electrolyte contained 1.0 mol L -1 The concentration of LiTFSI was 0.1 mol L -1 The LiNO3 is prepared, and the solvent is a mixture of DOL and DME in a volume ratio of 1:1; the diaphragm is a commercial Celgard 2400 type, and the negative electrode sheet used is a commercial lithium sheet; the positive electrode sheet and the diaphragm, the negative electrode sheet, and the battery electrolyte are assembled in a glove box with a protective atmosphere to prepare a lithium-sulfur battery.

[0052] Performance Testing:

[0053] 1) Test electron microscope image

[0054] Figure 1 is the solid-state NMR carbon spectrum of viologen-based conjugated porous polymer (TCV); Figure 1 It can be seen that the peak of TCV spectrum at 167ppm is the carbon peak on the triazine ring, and the other seven peaks can be attributed to the skeleton carbon peaks of viologen derivatives, proving that cyanuric chloride (TCT) and viologen derivatives (V·2Cl) undergo condensation reaction.

[0055] Figure 2 TEM image of TCV@CNT prepared in Example 1; Figure 2 The TEM images confirmed the successful growth of TCV on the CNT surface.

[0056] 2) Cyclic voltammetry test of symmetrical battery

[0057] The TCV@CNT of step S1 of Example 1, the TCV+CNT of comparative example 3, the untreated CNT and the TCV of comparative example 3 were ground and mixed with PVDF at a mass ratio of 9:1, and an appropriate amount of NMP was added to form a mixed slurry. The slurry was scraped on a carbon paper current collector as a working electrode and a counter electrode. The electrolyte of the symmetrical cell (0.2M Li2S6 solution) was obtained by dissolving elemental sulfur (S8) and Li2S in a commercial electrolyte at a molar ratio of 5:8. The assembled symmetrical cell was subjected to CV testing on an electrochemical workstation. The voltage range of the CV curve was -1.5 to 1.5 V, and the scan rate was 10 mV s -1 .

[0058] Figure 3 CV curves of symmetrical batteries assembled with TCV@CNT, TCV+CNT, CNT and TCV respectively; Figure 3It can be seen that the symmetrical battery assembled with TCV@CNT has the highest reduction onset potential and peak current, showing the highest rate of lithium polysulfide conversion, indicating that the nanopolymer TCV@CNT in situ grown on the CNT surface can more efficiently promote the redox conversion of lithium polysulfide.

[0059] 3) Cyclic stability test:

[0060] The battery cycle stability test was carried out on the Wuhan Blue Electric multi-channel battery testing system. The voltage range of the battery charge and discharge test was 2.8 to 1.7V, and the test was carried out at a current of 0.2C.

[0061] Figure 4 The charge-discharge cycles of S / TCV@CNT, S / TCV+CNT, S / CNT and S / TCV at 0.2C; Figure 4 It can be seen that the S / TCV@CNT positive electrode shows the highest initial discharge specific capacity and the lowest specific capacity decay rate within 100 charge and discharge cycles, proving the excellent electrochemical performance of TCV@CNT.

[0062] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a positive electrode material for a battery, characterized in that: The following steps are involved: S1. Take 1,1'-bis(4-aminophenyl)-[4,4'-bipyridyl]-1,1'-diammonium chloride and record it as V·2Cl. Add cyanuric chloride, V·2Cl and carbon nanotubes (CNT) into a solvent and mix them evenly. Solvothermal reaction occurs. Viologen-based conjugated porous polymer grows on the surface of carbon nanotubes (CNT) by in-situ directional polymerization. The product is recorded as TCV@CNT. S2. Grind TCV@CNT and sublimated sulfur and add them into a reactor, fill the reactor with protective gas, and sulfurize TCV@CNT by melt diffusion method to obtain a battery positive electrode material, which is recorded as S / TCV@CNT.

2. The method for preparing a positive electrode material for a battery according to claim 1, characterized in that: In step S1, cyanuric chloride, V·2Cl and carbon nanotubes CNT are mixed in a mass ratio of 1:3.35:3.7, and then anhydrous ethanol and DMF are added as solvents, wherein the volume ratio of anhydrous ethanol to DMF in the solvent is 3:

2.

3. The method for preparing a positive electrode material for a battery according to claim 1 or 2, characterized in that: In step S1, the temperature of the solvent thermal reaction is 120° C. and the reaction time is 3 days. After cooling to room temperature, the mixture is filtered to obtain black powder TCV@CNT.

4. The method for preparing a positive electrode material for a battery according to claim 1, characterized in that: In step S2, TCV@CNT and sublimated sulfur are ground and mixed at a mass ratio of 4:

6.

5. The method for preparing a positive electrode material for a battery according to claim 1, characterized in that: In step S2, the reactor is a stainless steel reactor lined with polytetrafluoroethylene, the reaction temperature in the reactor is 155°C, and the reaction time is 12h.

6. A battery positive electrode material obtained by the method for preparing a battery positive electrode material according to any one of claims 1 to 5.

7. A lithium-sulfur battery made from the battery positive electrode material according to claim 6.

8. A method for preparing a lithium-sulfur battery according to claim 7, characterized in that: The method comprises the following steps: grinding and mixing a battery positive electrode material S / TCV@CNT and a binder PVDF in a mass ratio of 9:1, adding N-methylpyrrolidone, grinding evenly to obtain a paste mixture, scraping the paste mixture onto a carbon paper current collector, and drying at 50-60°C for 10-12 hours to obtain a positive electrode sheet; and assembling the positive electrode sheet with a diaphragm, a negative electrode sheet, and a battery electrolyte in a glove box with a protective atmosphere to obtain a lithium-sulfur battery.

9. The method for preparing a lithium-sulfur battery according to claim 8, characterized in that: The battery electrolyte contains 1.0 mol L -1 The concentration of LiTFSI was 0.1 mol L -1 The solvent is a mixture of dioxolane DOL and ethylene glycol dimethyl ether DME in a volume ratio of 1:

1.

10. The method for preparing a lithium-sulfur battery according to claim 8, characterized in that: The separator used is the commercial Celgard 2400 type, and the negative electrode sheet used is a commercial lithium sheet.

Citation Information

Patent Citations

  • Application of additive in viologen water-phase organic flow battery

    CN115084524A

  • High-stability organic polymer electrode, preparation method thereof and battery using high-stability organic polymer electrode

    CN116247164A

  • Silicon-based negative electrode active material surface-modified with indium, negative electrode and lithium secondary battery comprising the same

    KR1020250058146A

  • Use of a battery with polyviologen active material

    US20200152984A1

  • Method for preparing complex cathode material for lithium sulfur battery, and lithium sulfur battery comprising complex cathode material prepared thereby

    WO2024210309A1

Cited By

  • Positive electrode material based on nitrogen-rich porous organic polymer as well as preparation method and application of positive electrode material

    CN122338061A